Study of strength training on swimming performance. A systematic review - González, L. R.; Melguizo-Ibáñez, E.; Martín-Moya, R.; González-Valero, G. (Science & Sports, 2023)
Aims Strength training is not usually an important aspect of the training programme for swimmers. Instead, more emphasis is placed on traditional swimming training, which focuses mainly on endurance work.